2005
DOI: 10.1182/blood-2004-07-2893
|View full text |Cite
|
Sign up to set email alerts
|

P2Y1 and P2Y12 receptors for ADP desensitize by distinct kinase-dependent mechanisms

Abstract: Adenosine 5-diphosphate (ADP) plays a central role in regulating platelet function by the activation of the G protein-coupled receptors P2Y 1 and P2Y 12 . Although it is well established that aggregation responses of platelets to ADP desensitize, the underlying mechanisms involved remain unclear. In this study we demonstrate that P2Y 1 -and P2Y 12 -mediated platelet responses desensitize rapidly. Furthermore, we have established that these receptors desensitize by different kinase-dependent mechanisms. G prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
205
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(224 citation statements)
references
References 45 publications
14
205
3
2
Order By: Relevance
“…The in vivo consequence is that under conditions of platelets refractory to stimulation by ADP, the P2Y 12 receptor remains functional and able to promote their reactivity at sites of injury, thus preventing loss of haemostatic function. On the other hand, it is reported that both P2Y 1 and P2Y 12 receptors undergo desensitization, and that P2Y 12 desensitization is mediated by G proteincoupled receptor kinases (GRK) [93,94]. Further studies are required to solve the apparent contradiction of these reports.…”
Section: Desensitizationmentioning
confidence: 99%
“…The in vivo consequence is that under conditions of platelets refractory to stimulation by ADP, the P2Y 12 receptor remains functional and able to promote their reactivity at sites of injury, thus preventing loss of haemostatic function. On the other hand, it is reported that both P2Y 1 and P2Y 12 receptors undergo desensitization, and that P2Y 12 desensitization is mediated by G proteincoupled receptor kinases (GRK) [93,94]. Further studies are required to solve the apparent contradiction of these reports.…”
Section: Desensitizationmentioning
confidence: 99%
“…PAR4 binds thrombin with much lower affinity, but it also internalizes more slowly and thus generates a steady and sustained integrin activation signal[1618]. Similarly, the ADP receptor P2Y1, which is not very abundant on the platelet surface[19], is rapidly desensitized[20,21]. Thus, it can only cause a rapid but short-lived rise of the cytosolic calcium concentration and needs co-signaling through the P2Y12 receptor to support platelet aggregation[22,23].…”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CImentioning
confidence: 99%
“…In order to minimize inappropriate platelet recruitment and activation at the site of a growing thrombus, platelet ADP responsiveness is tightly regulated in human platelets (8)(9)(10)(11)(12). P2Y 12 receptor responsiveness rapidly desensitizes in human platelets (13).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…P2Y 12 receptor responsiveness rapidly desensitizes in human platelets (13). Previous studies in cell lines have identified that G protein-coupled receptor kinase (GRK)2-and GRK6-dependent phosphorylation of the P2Y 12 receptor is required for arrestin association and desensitization (9).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation